Influence of TNF-alpha on the efficacy of anemia correction in patients with lymphoproliferative disorders - N. A. Romanenko; S. S. Bessmeltsev; O. E. Rozanova; N. S. Karpova; K. M. Abdulkadyrov (Онкогематология, 2022)
In this article mechanisms of anaemia development in patients with lymphatic tissue malignant diseases are presented. Therapy efficacy of erythropoiesis-stimulating agents (EPO) in patients with lymphoproliferative disorders and anaemia (n = 21) is studied. Study group included patients with a chronic lymphoid leukemia (n = 5), indolent lymphomas (n = 7) and multiple myeloma (n = 9). Patients were 49–80 years of age (63.6 ± 8.2 years). The positive response to EPO therapy was considered if hemoglobin level increased on 20 g/l or its rising to 120 g/l. With given therapy hemoglobin level was increased from 86.8 ± 18.5 g/l to 111.4 ± 26.5 g/l (p < 0.001). EPO therapy efficacy was 61.9 % for total group of patients. Importance of TNF-alpha detection as the prognosis factor of EPO therapy efficacy was studied. Patients with low level of TNF-alpha (less than 15 pg/ml) achieved the positive response in 92.9 %, with a high level of TNF-alpha (more than 15 pg/ml) – the positive response was not observed. Inversely proportional correlation between initial TNF-alpha level and therapy response has been established (r = -0.487; p < 0.03; n = 21). Thus, detection of TNF-alpha level in patients with lymphoproliferative disorders before EPO therapy allows to predict therapy response with high degree of significance.